Mechanical and Fracture Properties of Nano-filler-Cellulose Fibre-reinforced Epoxy Nanocomposites - Alamri, Hatem; Low, It-Meng (Engineers Australia, 2010)
Natural fibre reinforced composites have attracted the attention of researchers because of their desirable properties in terms of toughness, high modulus, low density, recyclability and renewability. In fact, the use of natural fibres in polymer composites has the potential to produce materials with higher specific strength and specific modulus due to their low density. Likewise, polymer composites reinforced with nano-filler have been widely investigated for their unique and significant improvement in strength, modulus, impact strength, barrier properties, heat resistance and thermal stability. In this paper, epoxy eco-composites reinforced with recycled cellulose fibres (RCF) and nano-fillers such as nano-clay platelets (30B), halloysite nanotubes (HNTs) and nano-silicon carbide (SiC), have been fabricated and investigated. The influences of RCF/nano-filler dispersion on the mechanical and fracture properties of these composites have been characterized in terms of flexural strength, flexural modulus, fracture toughness and impact-fracture.It was found that the presence of RCF resulted in significant increase in fracture toughness, impact strength, impact toughness and flexural modulus but moderate increase in flexural strength. However, the influence of nano-filler on flexural strengths was found to be modest or insignificant which could be due to the poor dispersion of nano-fillers and the existence of voids within the samples. Addition of RCF was found to increase the porosities of all composites.